Legal Theory and Gendered History - Kessler-Harris, Alice (Columbia Journal of Gender and Law, 2010)
As a group, historians tend to be, if not anti-theoretical, at least atheoretical. We back away from developing theory, although we shamelessly adopt and adapt it and frequently invoke it to legitimize our interpretations. Marx, Freud, Foucault and Martha Nussbaum have all entered our work. Historians tend to use theory to sustain flimsy or controversial evidence-to provide the scaffolding that supports our conclusions. My comments in this Article address how we do that. How do we test abstract and thinly rooted theoretical frames against historical evidence that has often been carefully amassed and allowed to speak only for itself? How, specifically, do we do that with the work of Martha Nussbaum? For those of us who work on gender, Nussbaum’s work has played a crucial role. We rely on books like Nussbaum’s Sex and Social Justice as a guide. When we want to think about what liberalism means for women in the contemporary world, we turn to Martha Nussbaum. And when we get involved in debates about cultural relativism, it is Martha we turn to. We do so not because only a few people write cogently about feminist theory; rather, we do so because few scholars approach feminist theory with both anecdotal knowledge and legal expertise. Let me try to explain why that is important. Martha’s work has been guided by an effort to explore questions of values in general, and, in particular, questions of how aspirations to achieve a good society influence American law, international law, and public policy. But the historian who admires that goal also pauses to push the question a step further. How, we ask of Martha, do you understand the meaning of “good”? Historians might rephrase the question to ask, what does “the good” mean in any given society at a particular moment in time? Who defines “the good”? Who sets its boundaries? How is “the good” realized under particular historical circumstances? How is it rewarded? How does a particular image of “the good” produce particular behaviors, and under what conditions?